Immune thrombocytopenic purpura associated with pulmonary tuberculosis - Akyıldız, Başak; Uzel, Nedret; Yanni, Diana; Çitak, Agop; Karaböcüoğlu, Metin; Üçsel, Raif (The Turkish Journal of Pediatrics, 2009)
Over the past decade, tuberculosis has been recognized worldwide as a public health problem of increasing proportions. We report a patient who presented with epistaxis and generalized petechiae. The diagnosis was immune thrombocytopenia and the patient was treated with intravenous immunoglobulin and pulse steroid. The bleeding continued and thrombocyte level was low despite therapy. Chest X-ray and a computed tomography scan of the thorax showed right upper lobe opacities and bilateral interstitial infiltrates. The patient also had a history of close contact with an individual with active tuberculosis. The thrombocytopenia was resistant to standard therapy, but resolved after antituberculosis treatment. This report is the first case of a child with immune thrombocytopenia secondary to pulmonary tuberculosis.